Respuesta :
ANSWER
[tex]x = \frac{1}{2} [/tex]
EXPLANATION
The given exponential equation is
[tex] {9}^{x + 1} = 27[/tex]
The greatest common factor of 9 and 27 is 3.
We rewrite the each side of the equation to base 3.
[tex]{3}^{2(x + 1)} = {3}^{3} [/tex]
Since the bases are equal, we can equate the exponents.
[tex]2(x + 1) = 3[/tex]
Expand the parenthesis to get:
[tex]2x + 2 = 3[/tex]
Group similar terms
[tex]2x = 3 - 2[/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
For this case we must solve the following equation:
[tex]9 ^ {x + 1} = 27[/tex]
We rewrite:
[tex]9 = 3 * 3 = 3 ^ 2\\27 = 3 * 3 * 3 = 3 ^ 3[/tex]
Then the expression is:
[tex]3^ {2 (x + 1)} = 3 ^ 3[/tex]
Since the bases are the same, the two expressions are only equal if the exponents are also equal. So, we have:
[tex]2 (x + 1) = 3[/tex]
We apply distributive property to the terms within parentheses:
[tex]2x + 2 = 3[/tex]
Subtracting 2 on both sides of the equation:
[tex]2x = 3-2\\2x = 1[/tex]
Dividing between 2 on both sides of the equation:
[tex]x = \frac {1} {2}[/tex]
Answer:
[tex]x = \frac {1} {2}[/tex]